Biodiesel exhaust: The need for a systematic approach to health effects research - Larcombe, A.; Kicic, A.; Mullins, Ben; Knothe, G. (Blackwell Publishing, 2015)
© 2015 Asian Pacific Society of Respirology. Biodiesel is a generic term for fuel that can be made from virtually any plant or animal oil via transesterification of triglycerides with an alcohol (and usually a catalyst). Biodiesel has received considerable scientific attention in recent years, as it is a renewable resource that is directly able to replace mineral diesel in many engines. Additionally, some countries have mandated a minimum biodiesel content in all diesel fuel sold on environmental grounds. When combusted, biodiesel produces exhaust emissions containing particulate matter, adsorbed chemicals and a range of gases. In many cases, absolute amounts of these pollutants are lower in biodiesel exhaust compared with mineral diesel exhaust, leading to speculation that biodiesel exhaust may be less harmful to health. Additionally, engine performance studies show that the concentrations of these pollutants vary significantly depending on the renewable oil used to make the biodiesel and the ratio of biodiesel to mineral diesel in the fuel mix. Given the strategic and legislative push towards the use of biodiesel in many countries, a concerning possibility is that certain biodiesels may produce exhaust emissions that are more harmful to health than others. This variation suggests that a comprehensive, systematic and comparative approach to assessing the potential for a range of different biodiesel exhausts to affect health is urgently required. Such an assessment could inform biodiesel production priorities, drive research and development into new exhaust treatment technologies, and ultimately minimize the health impacts of biodiesel exhaust exposure.